Relación del color y las características fisiológicas y fisicoquímicas del rocoto (capsicum pubescens) - Sánchez Cerna, Jesús Ronal (2015)
The overall objective of this work is to determine the relationship between color and the physiological and physicochemical characteristics of hot pepper (Capsicum pubescens) , so we can predict certain features only know the parameters rocoto color . Rocoto Huamachuco was used to carry out this work, in which a selection and sorting of raw material according to its maturity was done ; green, ripening fruit , ripe and overripe , taking five samples for each condition. Parameters determined color (a * , b * and L ) with the digital colorimeter ; the specific physiological characteristics were: respiration rate CO2 sensors ( mgCO2 / kg h ) and O2 ( mg O2 / kg h ) , from these respiratory quotient (RQ ) was calculated , the transpiration rate was determined by difference weight. As long as certain physicochemical characteristics were: Brix refractometer, pH with a pH meter and titratable acidity. The relationship between color and physiological and physicochemical characteristics was evaluated using the multiple regression analysis through the Pearson correlation coefficient (r) and the coefficient of determination (R2) . It was determined that the pH increases as the product matures, so does the Brix and% acidity. In addition it was found that there is a significant positive relationship between Brix and acidity with rocoto color parameters but not for the other characteristics. Keywords: Capsicum